Teachers, loosen up! How teachers can trigger interpersonally cooperative behavior in students at risk of academic failure. (December 2022) - van Vemde, Lian; Donker, Monika H.; Mainhard, Tim
Abstract: Student cooperativeness underlies high quality teacher-student relationships, and has been positively associated with students' school engagement. Fostering cooperative rather than oppositional student behavior might be especially helpful for protecting at-risk students against academic failure. To understand how exactly students' cooperativeness can be fostered, we investigated the interpersonal behaviors of secondary school teachers and at-risk students during dyadic interactions ( N = 82 dyads) in the context of positive teacher-student relationships. Using Continuous Assessment of Interpersonal Dynamics, moment-to-moment teacher and student behavior was captured in terms of interpersonal agency (dominance vs. submissiveness) and communion (opposition vs. cooperation). Time-series analyses were used to analyze interpersonal behavior within individuals, within dyads, and between dyads. Cooperative student behavior was most likely if teachers acted friendly and cooperatively and if teachers 'loosened up' their agency and the structure they imposed on the interaction repeatedly, which may give students more freedom to express themselves and to cooperate. Highlights: Dyadic interaction between at-risk students and their favorite teacher was assessed. Observations captured both agency and communion of teachers and students. Student cooperation was fostered by teacher cooperation. Students were more cooperative when teachers showed flexibility in agency. When fostering student cooperation both communion and agency are important.